Nutrient content, antioxidant activity, and organoleptic quality of coriander seeds (Coriandrum sativum L.) and white ginger (Zingiber officinale Rosc.) tea bags as functional drinks for hypertension - Kamilah, Abidah Hana; Pudjirahaju, Astutik; Razak, Maryam (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2025)
Background: High blood pressure prevalence in Indonesia increased to 34.1% in 2018.  High blood pressure can be caused by an unhealthy diet, including high sodium intake.  Therefore, potassium and antioxidant intake are needed to lower blood pressure.  Objectives: Analyzing the nutritional quality (moisture content, ash content, potassium content, and antioxidant activity) and organoleptic quality (colour, aroma, and taste) of coriander seeds and white ginger tea bags as functional drinks for hypertension.  Methods: The study used experimental research with Completely Randomized Design (CRD) using three treatment levels and three repetitions with ratio of coriander seeds and white ginger used in this study is P1 (55:45), P2 (50:50), and P3 (45:55).  Determinating organoleptic quality using hedonic and descriptive, water content using oven method, ash content using incineration method, potassium content using calculated value, and antioxidant activity using DPPH method.Results: Moisture content, ash content, and potassium content of each coriander seed and white ginger tea bag formulation have met the standards. The IC50 values in each coriander seed and white ginger tea bag indicate very strong antioxidant properties. Organoleptic quality results for colour indicate that P2 (50:50) has the highest value and significantly differs from P1 (55:45) and P3 (45:55) (p-value < 0.05), while for aroma and taste, P2 (50:50) has the highest value but no significant difference was observed (p-value>0.05). Conclusion: The best formulation of coriander seeds and white ginger tea bags as a functional drink for hypertension is P2 (50:50).